Conservative Treatment With Progestin and Pregnancy Outcomes in Endometrial Cancer. Issue 6 (1st July 2009) - Hahn, Ho-Suap; Yoon, Seok-Geun; Hong, Jae-Shik; Hong, Sung-Ran; Park, Sei-Jin; Lim, Jae-Yun; Kwon, Yong-Soon; Lee, In-Ho; Lim, Kyung-Taek; Lee, Ki-Heon; Shim, Jae-Uk; Mok, Jung-Eun; et al.
Abstract : Introduction: The purpose of this study was to evaluate the efficacy of conservative treatment with progestin and pregnancy outcomes in women with early-stage endometrial cancer. Methods: We retrospectively analyzed the medical records of 35 patients with endometrial adenocarcinoma, who were treated with progestin from January 1996 to December 2006. Women with early-stage grade 1 endometrioid endometrial adenocarcinoma, who wanted to receive conservative treatment or preserve fertility, were included. All women were treated with medroxyprogesterone acetate or megestrol acetate, with regular dilation and curettage performed. Complete remission (CR) was defined as no evidence of endometrial adenocarcinoma or hyperplasia. Partial remission was diagnosed when the patient developed endometrial hyperplasia, and persistent disease was defined as residual endometrial adenocarcinoma by pathologic confirmation. Results: The median age was 31 years (range, 21-43 years), and the median follow-up period was 39 months (range, 5-108 months). Complete remission was achieved in 22 patients (62.9%), partial remission was achieved in 1 patient (2.9%), and 12 patients (34.3%) had persistent disease. The median time to CR was 9 months (range, 2-12 months). Of the 22 patients with CR, 9 (40.9%) had recurrent disease, and the median time to recurrence was 12 months (range, 8-48 months). Ten (83.3%) of the 12 patients with CR who tried to conceive were successful, and 8 of the 10 pregnancies resulted in live births. There were no congenital anomalies in babies associated with progestin treatment. Conclusions: Conservative treatment with progestin can be considered a good therapeutic option in patients with well-differentiated early-stage endometrioid endometrial adenocarcinoma who wish to preserve their uteri or become pregnant.